A study of passenger handling practices at Pelangi Air Sendirian Berhad / Abdul Halim Hassan - Hassan, Abdul Halim (1994)
The best selling point any airline can have these days is for its passengers to have a good service experience which will encourage repeat patronage. The quest to lure passengers is seen more as a product rather than fare competition. For an airline company, providing quality service is important and should not be left to chance. Successful airlines have always placed quality service as one of their top criterion.